Minimization of time distribution of ballots with Greedy algorithms in Jombang Regency - Erina Seviyanti Dewi; Latifah Asmaul Fauzia (Journal of Natural Sciences and Mathematics Research, 2021)
Travelling Salesman Problem is a problem faced by salesmen in distributing goods by passing all points exactly once. This problem is often encountered in life, not least in the distribution of election ballots from the Komisi Pemilihan Umum Daerah (KPUD) Jombang office to the sub-district office in Jombang Regency. Proper route determination can help to minimize the travelling time between places so that the risk of delaying ballot distribution can be avoided. In determining the solution of Traveling Salesman Problem, a Hamiltonian cycle is required. The Hamiltonian cycle is a closed trail that passes every point exactly one time. The Hamilton cycle can be formed by the Greedy Algorithm. The Greedy Algorithm can quickly determine the next point based on the smallest weight in the form of distance between points. From the problem of ballot distribution in Jombang, the starting point of the route is the office of Komisi Pemilihan Umum Daerah (KPUD) Jombang then through 21 sub-district offices and back to the Komisi Pemilihan Umum Daerah (KPUD) office Jombang. Based on the searching for solutions to minimize the distribution time of ballots in Jombang Regency with Greedy Algorithm, the total distance to pass all existing sub-district offices is 253.1 km with a travel time of 427 minutes or 7 hours 7 minutes.©2021 JNSMR UIN Walisongo. All rights reserved.